The System of Formation of Lexical Competence - Yarieva Z.Sh (Genius Journals, 2023)
This article provides theoretical knowledge about the development of lexical competence of 2nd year students of Linguistics in accordance with various teaching principles. Principles affecting lexical competence have been developed.
Keywords: Lexical competence; lexical units; formation; motivation